β-N-Acetylhexosaminidases-the wizards of glycosylation - Bojarová, Pavla; Bruthans, Jan; Křen, Vladimír (Applied microbiology and biotechnology, 2019)
β-N-Acetylhexosaminidases (EC 3.2.1.52) are a unique family of glycoside hydrolases with dual substrate specificity and a particular reaction mechanism. Though hydrolytic enzymes per se, their good stability, easy recombinant production, absolute stereoselectivity, and a broad substrate specificity predestine these enzymes for challenging applications in carbohydrate synthesis. This mini-review aims to demonstrate the catalytic potential of β-N-acetylhexosaminidases in a range of unusual reactions, processing of unnatural substrates, formation of unexpected products, and demanding reaction designs. The use of unconventional media can considerably alter the progress of transglycosylation reactions. By means of site-directed mutagenesis, novel catalytic machineries can be constructed. Glycosylation of difficult substrates such as sugar nucleotides was accomplished, and the range of afforded glycosidic bonds comprises unique non-reducing sugars. Specific functional groups may be tolerated in the substrate molecule, which makes β-N-acetylhexosaminidases invaluable allies in difficult synthetic problems.
Keywords: biokatalýza; Biocatalysis; Mutant Proteins; Oligosaccharide; N-acetylgalactosamine; beta-N-acetylhexosaminidasy; mutantní proteiny; Modified substrate; β-N-acetylhexosaminidase; glykosylace; Carbohydrate; Glycosylation; N-acetylglucosamine; Glycosidase; Enzymatic synthesis; beta-N-Acetylhexosaminidases